2022
DOI: 10.1111/aas.14115
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and adverse events of hemoadsorption with CytoSorb® in critically ill patients: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Background: The effects and safety of extracorporeal hemoadsorption with CytoSorb ® in critically ill patients with inflammatory conditions are controversial.Methods: We performed a systematic review with meta-analysis and trial sequential analysis (TSA) of randomized-controlled trials to assess the mortality and safety of CytoSorb ® therapy in critically ill patients with inflammatory conditions. Electronic databases were searched up to April 2022. The primary outcome was mortality at longest follow-up and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…In a systematic review including 5 RCTs ( n = 163 patients) evaluating ECAT in cardiac surgery, Goetz et al reported no significant benefits from the technique in terms of mortality and post-operative complications [ 148 ]. Moreover, a recent meta-analysis of 8 trials in sepsis and 10 in cardiac surgery (total 875 patients), revealed (low certainty of evidence) that the use of a cytokine filter might increase mortality in critically ill patients with inflammatory conditions [ 149 ]. As a whole, these data indicate that the efficacy and safety of ECAT remains not established.…”
Section: Managementmentioning
confidence: 99%
“…In a systematic review including 5 RCTs ( n = 163 patients) evaluating ECAT in cardiac surgery, Goetz et al reported no significant benefits from the technique in terms of mortality and post-operative complications [ 148 ]. Moreover, a recent meta-analysis of 8 trials in sepsis and 10 in cardiac surgery (total 875 patients), revealed (low certainty of evidence) that the use of a cytokine filter might increase mortality in critically ill patients with inflammatory conditions [ 149 ]. As a whole, these data indicate that the efficacy and safety of ECAT remains not established.…”
Section: Managementmentioning
confidence: 99%
“…A systematic review and meta-analysis of randomized controlled trials by Heymann M, et al (June 2022) about mortality and adverse events of hemoadsorption concluded that considerable uncertainty about the findings do not allow firm conclusions and suggest the need of further high-quality randomized trials before systematic use of Cytosorb hemoadsorption. (11)…”
Section: Aki During Covid-19 Pandemicmentioning
confidence: 99%
“…We understand that further trials are needed before the implementation of hemoadsorption in critically ill patients with or without COVID-19. A systematic review and metaanalysis of randomized controlled trials by Heymann et al about mortality and adverse events of hemoadsorption concluded that considerable uncertainty about the findings do not allow firm conclusions and suggest the need of further high-quality randomized controlled trials before systematic use of Cytosorb hemoadsorption (11).…”
Section: Epidemiologymentioning
confidence: 99%
“…4,[15][16][17][18] The latest published systematic review of randomized-controlled trials of therapy with CytoSorb in critically ill patients with inflammatory conditions showed no apparent benefits and at the same time risk of harm of hemoadsorption with CytoSorb. 19 We hypothesized that Cytosorb or Jafron therapy may benefit patients on V-A ECMO in terms of levels of inflammatory markers such as IL-6, complications, and overall outcomes. We report our experience in a single tertiary referral center in Kazakhstan with the use of blood purification in V-A ECMO-supported post-cardiotomy patients.…”
Section: Introductionmentioning
confidence: 99%